High-efficiency removal of benzene vapor using activated carbon from Althaea officinalis L. biomass as a lignocellulosic precursor - Isinkaralar, Kaan (Springer Science and Business Media LLC, 2022)
Benzene is a primary air pollutant commonly found widespread in the indoor environment. It has always been a research focus on the environment due to the causes of significant human health concerns. It has been widely utilized in the synthesis of solvent production, which can rarely be found in high concentrations in outdoor air or high amounts in indoor air, depending on its sources. It is aimed to remove different initial benzene concentrations (from 5 to 1500 ppm) with the production of activated carbon as an excellent adsorbent with a high surface area to be used in these situations. Lignocellulosic wastes have great potential for activated carbon for their advantages (abundant, recycled, and low-cost materials, etc.). This study aimed to evaluate biowaste material for activated carbon production from Althaea officinalis L. biomass by chemical activation (H2SO4, LiOH, and ZnCl2) at temperatures between 500 and 900 °C. Newly developed powdered activated carbons (Ao-ACs) are also tabulated as Ao-AC1-45 for easy reference. Benzene vapor was collected into Tenax TA® tubes by automatic thermal desorption in conjunction with a capillary gas chromatography-mass spectrometry (TD-GC/MS). The significant surface area and production yield of Ao-ACs were obtained at 1424 m2/g (Ao-AC43) and up to 40.32%, respectively. The maximum gas-phase benzene adsorption capacity was 140 mg/g at 270 min. This research has focused on adsorption gas-phase benzene removal onto Ao-ACs as a low-cost adsorbent from the Althaea officinalis L. biomass. Conspicuously, more study is needed to perform the enhanced adsorption of airborne pollutants capacity with inexpensive activated carbon from waste biomass materials.
Keywords: Waste Products; Air Pollutants; Benzene; Lignin; Althaea; Charcoal; Solvents; Humans; Adsorption; Biomass; Gases; 7. Clean energy; 12. Responsible consumption; 13. Climate action